Pediatric airway surgery management of laryngotracheal stenosis in infants and children - Monnier, Philippe (Springer eBooks., 2011)
This book provides detailed insight into the difficult problem of pediatric airway management. Each chapter focuses on a particular condition in a very practical manner, describing diagnostic procedures and precisely explaining surgical options with the help of high-quality illustrations. Both established treatment modalities and new management concepts are considered in depth, and controversies relating to the most difficult airway reconstructions are discussed. To help the reader, boxes are included to summarize procedures and to list tips, tricks, and traps relevant to daily practice.